2024
DOI: 10.5599/admet.2268
|View full text |Cite
|
Sign up to set email alerts
|

Berberine HCl and diacerein loaded dual delivery transferosomes: Formulation and optimization using Box-Behnken design

Siddharth Singh,
Rajendra Awasthi

Abstract: Introduction: Berberine is a poorly water-soluble alkaloid compound showing significant anti-inflammatory characteristics. It reduces the levels of pro-inflammatory and inflammatory cytokines, including tumour necrosis factor (TNF-????, IFN-????) and interleukin (IL-23, IL-12, and IL-23). Diacerein significantly reduces the splenomegaly associated with psoriasis. It downregulates the production of TNF-α and IL-12. Method: This study reported the development of transferosomes containing berberine HCl and diacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Edge activators have remarkable deformability and flexibility, allowing them to easily pass through the biological membranes. 15 In a recent study, Mirza et al reported improved brain targeting efficiency of cefepime-loaded transferosomes via the intranasal route. 16 Salem et al developed donepezil hydrochloride-loaded nanotransferosomes for the treatment of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Edge activators have remarkable deformability and flexibility, allowing them to easily pass through the biological membranes. 15 In a recent study, Mirza et al reported improved brain targeting efficiency of cefepime-loaded transferosomes via the intranasal route. 16 Salem et al developed donepezil hydrochloride-loaded nanotransferosomes for the treatment of AD.…”
Section: Introductionmentioning
confidence: 99%